2020
DOI: 10.1177/1457496920925637
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus conventional laparoscopic liver resections: A systematic review and meta-analysis

Abstract: Background: Theoretical advantages of robotic surgery compared to conventional laparoscopic surgery include improved instrument dexterity, 3D visualization, and better ergonomics. This systematic review and meta-analysis aimed to determine advantages of robotic surgery over laparoscopic surgery in patients undergoing liver resections. Method: A systematic literature search was conducted for studies comparing robotic assisted or totally laparoscopic liver resection. Meta-analysis of intraoperative (operative ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 69 publications
2
50
2
2
Order By: Relevance
“…Compared to open (n = 10 146) and laparoscopic (n = 520) hepatectomy, robotic procedures (n = 204) were associated with a shorter length of stay and less frequent non-elective readmission within 45 days. Same results were reported in two recent meta-analyses by Kamarajah et al as well as by Gavriilidis et al revealing significantly lower readmission rate for robotic compared with laparoscopic liver resections [13,31]. All of this provide evidence of favorable recovery in patients undergoing robotic liver resection as evident by reduced complications, lower rates of intensive care unit admissions, shorter length of stay and less frequent non-elective readmissions.…”
Section: Enhanced Recovery a Key Step In Reducing Cost And Improvingsupporting
confidence: 78%
See 1 more Smart Citation
“…Compared to open (n = 10 146) and laparoscopic (n = 520) hepatectomy, robotic procedures (n = 204) were associated with a shorter length of stay and less frequent non-elective readmission within 45 days. Same results were reported in two recent meta-analyses by Kamarajah et al as well as by Gavriilidis et al revealing significantly lower readmission rate for robotic compared with laparoscopic liver resections [13,31]. All of this provide evidence of favorable recovery in patients undergoing robotic liver resection as evident by reduced complications, lower rates of intensive care unit admissions, shorter length of stay and less frequent non-elective readmissions.…”
Section: Enhanced Recovery a Key Step In Reducing Cost And Improvingsupporting
confidence: 78%
“…Guan et al analyzed pooled data from 435 robotic and 503 laparoscopic cases and found a significantly increased blood loss in the robotic cohort [37]. This is in contrast to recent meta-analyses by Kamarajah et al, including 2630 patients (950 robotic and 1680 laparoscopic cases) undergoing liver resection, revealing a significantly reduced estimated blood loss with no differences in transfusion rates between robotic and laparoscopic liver resection [31]. Among the possible explanations for the apparently conflicting finding regarding intraoperative blood loss is the mixed population of major and minor resections, with a trend to more extensive resections in the robotic cohorts.…”
Section: Short-term Outcomesmentioning
confidence: 94%
“…However, no significant differences were found in conversion rates, transfusion rates, complications, bile leaks, or length of hospital stay between these surgeries. 19 Moreover, robotic surgery had a significantly lower readmission rate compared with laparoscopic surgery (odds ratio = 0.43; P < .01). 19 These findings reaffirm our findings that robotic surgery has an equivalent short-term outcome compared with laparoscopic surgery in treating early-stage HCC.…”
Section: Resultsmentioning
confidence: 92%
“…However, there is one thing worthy of our attention that patients undergoing robotic liver resection have a higher readmission rates (P = 0.005), Compared with traditional open surgery, minimally invasive surgery (robot and laparoscopic) is more expensive, but there is no statistical difference. It can significantly reduce intraoperative blood loss and shorten the length of stay; the tumor volume of patients undergoing laparoscopic liver resection was significantly reduced than patients in the open surgery group [47][48][49] . Minimally invasive surgery for HCC is not a simple minimally invasive technology, but a process of minimally invasive concept and comprehensive treatment.…”
Section: Resultsmentioning
confidence: 99%